Influence of Dexmedetomidine on Post-operative Atrial Fibrillation After Cardiac Surgery: A Meta-Analysis of Randomized Controlled Trials - Peng, Sheng; Wang, Juan; Yu, Hui; Cao, Ge; Liu, Peirong (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous clinical studies and meta-analysis evaluating the influence of dexmedetomidine on postoperative atrial fibrillation showed inconsistent results. We performed an updated meta-analysis to evaluate the influence of dexmedetomidine on incidence of postoperative atrial fibrillation after cardiac surgery. Methods: Randomized controlled trials that evaluated the potential influence of dexmedetomidine on the incidence of atrial fibrillation after cardiac surgery were obtained by search of PubMed, Embase, and Cochrane's Library databases from inception to April 12, 2021. A random-effects model incorporating the potential publication bias was used to pool the results. Influences of patient or study characteristics on the efficacy of dexmedetomidine on atrial fibrillation after cardiac surgery were evaluated by meta-regression and subgroup analyses. Results: Fifteen studies with 2,733 patients were included. Pooled results showed that dexmedetomidine significantly reduced the incidence of atrial fibrillation compared to control (OR: 0.72, 95% CI: 0.55–0.94, p = 0.02) with mild heterogeneity (I2 = 26%). Subgroup analysis showed that dexmedetomidine significantly reduced the incidence of atrial fibrillation in studies from Asian countries (OR: 0.41, 95% CI: 0.26–0.66, p < 0.001), but not in those from non-Asian countries (OR: 0.89, 95% CI: 0.71–1.10, p = 0.27; p for subgroup difference = 0.004). Meta-regression analysis showed that the mean age and proportion of male patients may modify the influence of dexmedetomidine on POAF (coefficient = 0.028 and 0.021, respectively, both p < 0.05). Subgroup analysis further showed that Dex was associated with reduced risk of atrial fibrillation after cardiac surgery in studies with younger patients (mean age ≤ 61 years, OR = 0.44, 95% CI: 0.28–0.69, p = 0.004) and smaller proportion of males (≤74%, OR = 0.55, 95% CI: 0.36–0.83, p = 0.005), but not in studies with older patients or larger proportion of males (p for subgroup difference = 0.02 and 0.04). Conclusions: Current evidence supports that perioperative administration of dexmedetomidine may reduce the risk of incidental atrial fibrillation after cardiac surgery, particularly in Asians.